Flexural fatigue analysis of plain and glass fibre reinforced polymer concrete composites - Bedi, Raman; Singh, S.P. (Journal of Structural Engineering, 2024)
Results of an investigation conducted to study the flexural fatigue of epoxy resin based Polymer Concrete Composites (PCC) and Glass Fibre Reinforced Polymer Concrete Composites (GFRPCC) are reported. Three point flexural fatigue tests were conducted on PCC and GFRPCC specimens using MTS servo controlled cyclic load test setup to obtain the fatigue lives at different stress levels. One hundred and sixty four specimens of size 40 × 40 × 160 mm were tested in flexural fatigue. Sixty eight static flexural tests were also conducted to facilitate fatigue testing. As a pre-requisite to the analysis reported in this paper, it has been shown that the fatigue life of PCC and GFRPCC, at any stress level, can be modeled by the two-parameter Weibull distribution. The fatigue strength prediction models, representing S-N relationships have been examined and the material coefficients have been obtained for PCC and GFRPCC containing 0.5%, 1.0% and 2.0% glass fibres. Further, using Weibull distribution probability of failure has been incorporated into the fatigue life data of PCC and GFRPCC to develop S-N-Pf relationships, both graphically and analytically. The two million cycle endurance limits for PCC and GFRPCC containing different amount of glass fibres have also been estimated.